INTEGRASI MEDIA DIGITAL DALAM PEMBELAJARAN LITERASI DAN NUMERASI DI SEKOLAH DASAR MELALUI MODEL NESTED: - - Aulia Himmawati; Sunhaji (STKIP Subang, 2025)
This study aims to describe the integration of digital media within the nested-type integrated learning model as an effort to enhance literacy and numeracy skills among elementary school students. The underlying issue of this research lies in the limited implementation of technology within learning activities, even though it is an essential component of 21st-century instructional design; thus, the potential of digital media has not yet been fully optimized. This study employs a literature review method with documentation techniques, and data analysis consisting of data reduction, data display, and conclusion drawing, followed by triangulation to ensure the validity of the findings. The results indicate that digital media such as Quizizz, Canva, and KIPIN 4.0 have been utilized across various elementary grade levels and have proven effective in supporting literacy and numeracy enhancement through interactive content, digital books, adaptive exercises, and multimodal learning materials. However, the implementation still faces notable challenges, particularly regarding teachers’ limited technological competence and the insufficient availability of adequate and equitable digital facilities in schools. This study emphasizes that the successful integration of digital media within the nested learning model requires strong synergy among teachers, students, and policymakers through continuous professional development, improved digital literacy, and the provision of high-quality technological resources. These findings are expected to inform policy strengthening and the development of digital-based integrated learning practices aimed at improving literacy and numeracy outcomes in elementary education.